The Effects of Personal Pharmacogenetic Testing on the Effects of Pharmacy Student Perceptions of Knowledge and Attitudes Towards Precision Medicine - Dalga D Surofchy, PharmD (c); Sam Oh, PhD, MPH; Joshua Galanter, MD, MAS; Pin Xiang, PharmD; Megan Li, PhD (c); Su Guo, PhD; Tejal Desai, PhD; B Joseph Guglielmo, PharmD; Kathy Giacomini, PhD; Janel Long-Boyle, PharmD, PhD; Alan HB Wu, PhD; Esteban Burchard, MD, MPH (University of Minnesota Libraries Publishing, 2017)
Objective: To evaluate if pharmacy students' participation in personal pharmacogenetic (Pgx) testing enhances their knowledge and attitude towards precision medicine (PM). Methods: First-year pharmacy students were offered personalized pharmacogenetic testing as a supplement to a required curricular pharmacogenomics course. Ninety-eight of 122 (80%) students completed pre- and post-course surveys assessing knowledge and attitudes regarding PM; 73 students also volunteered for personal pharmacogenetic testing of the following drug metabolizing enzymes (CYP2C19, CYP2D6, UGT1A1) and pharmacodynamics-relevant proteins (interleukin (IL)-28B & human lymphocyte antigen HLAB*5701). Results: Among the 122 students, we found that incorporating pharmacogenetic testing improved mean knowledge and attitude by 1.0 and 0.3 Likert points, respectively. We observed statistically significant improvements in 100% of knowledge and 70% of attitude-related statements for students who decided to undergo personal pharmacogenetic testing. Students who were enrolled in the course but did not partake in personalized pharmacogenetic testing had similar gains in knowledge and attitude. Conclusion: This study demonstrates the feasibility and importance of educating future pharmacists by incorporating pharmacogenetic testing into professional school curricula. Students who opt not to participate in genotyping may still benefit by learning vicariously through the shared learning environment created by genotyped students. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties.   Type: Student Project